Quilombola confluences: the case of the community of Croatá (MG) - Moreira, Agda Marina; Heller, Léo; Silva, Priscila Neves (Argumentum, 2024)
This article results from dialogues with the quilombola, fishing, and floodplain (vazanteira) community of Croatá (MG), located in the municipality of Januária, in the northern region of Minas Gerais, Brazil. Since 2013, this community has been undertaking a process of reterritorialization, with the São Francisco River at its centre. Through collaborative research, we present aspects derived from participant observation and interviews conducted in the second half of 2023, interwoven with the relationship between health and territory. We present the perceptions of the research subjects regarding the territory, using the concept of “confluence”, coined by quilombola thinker Nego Bispo, as a guiding axis. Based on this, we analysed the relationships of struggles and affections formed by the community in defence of their territory, and the implications of this process for the health of quilombola subjects. As a result, we assert that quilombola health must take into consideration the specificities and the references of its subjects, and highlight the relevant aspects of their ways of knowing and doing. Therefore, thinking about health is only possible when associated with the territory. In this process, where memory and orality stand out, quilombola subjects must be heard and considered in any proposal for a health modality that includes them.